Johnny & Clyde [videorecording (DVD)] - DeNucci, Tom, 1984-; DeNucci, Tom, 1984-; Ritter, Tyson; Fox, Megan, 1986-; Jogia, Avan, 1992-; Russell, Ajani (2022)
Johnny (Avan Jogia) and Clyde (Ajani Russell) are two serial killers madly in love and on an endless crime spree. They set their sights on robbing a casino owned by the crime boss Alana (Megan Fox) and guarded by her demonic warrior --